2020
DOI: 10.1016/j.envres.2020.109812
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mental health effects of repeated short walks in a blue space environment: A randomised crossover study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 54 publications
(102 reference statements)
1
41
0
Order By: Relevance
“…Relevant studies have pointed out that after outdoor group walks, the perception of restorativeness and naturalness influence each other, thus enhancing the positive emotional experience [ 24 ]. In addition, walking is an enjoyable form of exercise that can alleviate individuals’ anxiety [ 40 , 41 , 42 ] and depression [ 8 , 43 ], and enhance their mental well-being [ 44 , 45 , 46 ]. Wensley et al [ 29 ] described walking as a kind of joy and considered it a source of positive emotions, and Kekäläinen et al [ 25 ] found that walking was associated with better psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have pointed out that after outdoor group walks, the perception of restorativeness and naturalness influence each other, thus enhancing the positive emotional experience [ 24 ]. In addition, walking is an enjoyable form of exercise that can alleviate individuals’ anxiety [ 40 , 41 , 42 ] and depression [ 8 , 43 ], and enhance their mental well-being [ 44 , 45 , 46 ]. Wensley et al [ 29 ] described walking as a kind of joy and considered it a source of positive emotions, and Kekäläinen et al [ 25 ] found that walking was associated with better psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Originally developed by McNair, Loor, and Droppleman in 1971 [ 47 ], this is a well-established, academic, and clinically validated measure of psychological distress and mental wellbeing consisting of 65 mood state questions grouped into 6 categories. POMS questionnaires have been used in a similar study that assessed the effects of medium-term exposure to blue and urban spaces on the mental health of participants undertaking various days of walking routines [ 23 ]. For this study, we used the 29-item version established by Fuentes et al (1995) [ 48 ], which divides mood states into 5 mood categories and explains 92.9% of the covariance of the original questionnaire: tension/anxiety (TA), depression (D), anger/hostility (AH), fatigue (F), and vigor (V).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that living or undertaking moderate physical activity near blue spaces such as the coast, lakes, or rivers is associated with better general health and wellbeing. It reduces anxiety and depression [ 17 , 18 , 19 ], creates opportunities for social interactions [ 4 ], and is linked to a better general mood [ 20 , 21 , 22 , 23 ]. However, the majority of these studies have focused on the salutogenic effects (i.e., the promotion and maintenance of physical and mental wellbeing) of being close to a water body, rather than being in direct contact with it.…”
Section: Introductionmentioning
confidence: 99%
“…Significant and increasing evidence demonstrates that walking and staying in an urban forest setting can bring mental wellbeing by generating positive emotions or countering negative emotions [12,13]. Relevant studies were usually conducted using a crossover design [14][15][16]. Therein, subjects in forest settings were taken as respondents while the controlled subjects spent time in urban settings and they would exchange routes the next day [14].…”
Section: Introductionmentioning
confidence: 99%